Afterwords. Issue 5 (October 2015) - Unknown
<x xml:space="preserve">Abstract</x> (see review in Educational Theory 65, no. 5 [2015]: 601‐608; Jane Roland Martin, Education Reconfigured: Culture, Encounter, and Change [London: Routledge, 2011])